Tablets Reveal Amorite Language (The Biblical archaeology review, 2023)
While the biblical writers remembered them as a legendary people of Canaan who had descended from giants (see p. 52), the Amorites were a nomadic people from Syria, first attested in the third millennium BCE, who became one of the most powerful groups within Mesopotamia. Indeed, many of the famous Mesopotamian kings from this period, […]